2016
DOI: 10.1037/tam0000074
|View full text |Cite
|
Sign up to set email alerts
|

Threat assessment and management in higher education in the United States: A review of the 10 years since the mass casualty incident at Virginia Tech.

Abstract: The April 16, 2007 mass casualty incident at Virginia Tech had an immediate, significant, and enduring impact on approaches to campus safety in the United States. In the aftermath of the incident, there were numerous campus safety reviews, not only at Virginia Tech, but across the Commonwealth of Virginia, across the nation, and around the world. Those reviews by campus administrations, state and federal government agencies, professional associations, victim advocacy groups, and law enforcement bodies, resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The first group of statements comprises those that followed crisis communications best practices by addressing those most affected by the crisis (Lawson, 2007), supporting underrepresented populations (Ulmer et al, 2015), and urging stakeholders to act in ways that promote self-aid and self-protection (Sellnow et al, 2015) by providing resources for the affected populations (Deisinger & Scalora, 2016). The second group of statements-representing 46.3% of the sample-condemned President Trump's actions without addressing DACA students or offering resources for these students.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first group of statements comprises those that followed crisis communications best practices by addressing those most affected by the crisis (Lawson, 2007), supporting underrepresented populations (Ulmer et al, 2015), and urging stakeholders to act in ways that promote self-aid and self-protection (Sellnow et al, 2015) by providing resources for the affected populations (Deisinger & Scalora, 2016). The second group of statements-representing 46.3% of the sample-condemned President Trump's actions without addressing DACA students or offering resources for these students.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Perhaps a watershed moment for critical examinations of crisis management in higher education, the 2007 Virginia Tech shooting-although categorized in this study as an emergency, not a crisis-produced a number of scholarly works that analyzed crisis management and institutional preparedness (Catullo, 2008;Deisinger & Scalora, 2016;Wang & Hutchins, 2010), touching upon Tierney's (1988) idea of reactive administrative responses before proactive administrative planning. Catullo (2008) found that important student affairs professionals believed their campuses to be prepared for a crisis in the wake of the 9/11 tragedy, yet research focused on the Virginia Tech incident "made it abundantly clear that there are many complicated facets of crisis preparation on residential university campuses that professionals may not be prepared to handle and the need to be proactive has never been greater" (p. vi).…”
Section: Crisis Management and Communication In Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this paradox is troubling, it should not prevent the establishment of such threat assessment teams in communities, educational settings, and corporate settings, because they work . In a few states in the United States, such threat assessment teams are required by law, particularly in educational settings, and were prompted by massacres such as the one at Virginia Tech in 2007 and Sandy Hook in 2012 . Threat assessment teams are also being established throughout Europe with the formation of multidisciplinary efforts in both universities and corporate settings.…”
Section: Discussionmentioning
confidence: 99%